1993
DOI: 10.1063/1.354212
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of the contribution of deep and shallow levels to the compensation mechanisms in annealed InP

Abstract: We have studied the effects of heat treatment under phosphorus atmosphere on the balance of electronic levels by capacitance-voltage and deep level transient spectroscopy measurements. A series of special samples was annealed under the conditions which we are normally using for the processing of nominally undoped semi-insulating (S.I.) InP. It is shown explicitly that in this annealing process the reduction of the free-carrier concentration is predominantly caused by a reduction of the net concentration of def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…15,16 Hirt et al have observed, by DLTS, in annealed but still conducting undoped InP, an electron trap having the same activation energy ͑0.4 eV͒ whose concentration increases with phosphorus pressure. 8,10 They as well observe in both undoped and Fe-doped annealed SI InP the same level by TSC. 10 In addition Zerrai et al 17 have reported the presence of a level named P3 having an activation energy ranging from 0.35 to 0.40 eV in Fe-doped SI InP and show that its concentration is not affected by the amount of Fe.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…15,16 Hirt et al have observed, by DLTS, in annealed but still conducting undoped InP, an electron trap having the same activation energy ͑0.4 eV͒ whose concentration increases with phosphorus pressure. 8,10 They as well observe in both undoped and Fe-doped annealed SI InP the same level by TSC. 10 In addition Zerrai et al 17 have reported the presence of a level named P3 having an activation energy ranging from 0.35 to 0.40 eV in Fe-doped SI InP and show that its concentration is not affected by the amount of Fe.…”
Section: Resultssupporting
confidence: 55%
“…observed. 23 They suggest that it could be due to a contamination during the annealing process. In our samples, the level at 0.6 eV is observed with a low concentration as compared to the other defects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Generally, thermally induced defects in the annealed material can be detected by different spectroscopy methods. [6][7][8] However, most of the reports so far 4-8 ͑including our previous work͒, 9 have been carried out in a single annealing run with high temperature and long duration. The defects in the material can only be detected in their final thermodynamic equilibrium states after long time annealing.…”
Section: ͓S0021-8979͑99͒07616-1͔mentioning
confidence: 99%
“…This implies clearly that wafer annealing at lower temperatures has an effect in reducing phosphorus vacancies. The mechanism of SI behavior has been extensively studied by various methods such as Mall effect [ 111,TSC[33], DLTS [34,35] and PL measurements [13,14]. The following three mechanisms have been proposed.…”
Section: Photoluminescence Examinationmentioning
confidence: 99%